1983
DOI: 10.1136/jnnp.46.7.620
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced emotional reactions in chronic head trauma patients.

Abstract: SUMMARY The emotional characteristics of head injury patients referred for neuropsychological testing were examined as a function of the time since injury. Patients referred more than 6 months from injury were more emotionally distressed on the MMPI and Katz Adjustment Scale (relatives form) compared to those tested 6 months or earlier. The more chronic head trauma patients were more anxious and depressed, more confused in their thinking, and more socially withdrawn compared to the acute patient group. These d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
3
2

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(73 citation statements)
references
References 13 publications
3
65
3
2
Order By: Relevance
“…In fact, by no means could we directly assess premorbid personality or verify whether close relatives evaluations reflected, for instance, real pre-TBI driving style. Prior research has shown that reports from caregivers on patients' functioning were more predictive of patients' fitness to drive than patients' self ratings [21,39]. Other findings suggested that relatives' own personality structure could impact upon their perception of the effects of brain injury on patients [90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, by no means could we directly assess premorbid personality or verify whether close relatives evaluations reflected, for instance, real pre-TBI driving style. Prior research has shown that reports from caregivers on patients' functioning were more predictive of patients' fitness to drive than patients' self ratings [21,39]. Other findings suggested that relatives' own personality structure could impact upon their perception of the effects of brain injury on patients [90].…”
Section: Discussionmentioning
confidence: 99%
“…Driving requires planning, concentration, inhibition of distractors, foresight, anticipation, problem-solving capacities, the ability to interpret rapidly complex arrays of multimodal stimuli, and prompt, effective, and calm reactions. Some post-TBI subjects display a hidden deficit in one or more of these domains and may have loss of emotional control under certain circumstances [35][36][37][38][39][40][41][42][43][44]. Others may also be unaware of 198 P. Pietrapiana et al…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Other frequent problems observed early postinjury and later concern the regulation of survival-oriented behavior, manifested in disinhibitory behavior (overeating, defensive behavior, changes in sexual behavior) [17][18][19][20][21] and of emotional state (indifference, irritability, excitation, incongruity of affect, emotional lability). [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In addition, a deficit in one or the other aspect of intentional, or goal-oriented behavior is also frequent, affecting appropriate understanding of the social environment and perception of oneself, goal formulation or identification of needs, determination and organization of steps and means of attaining the goal or satisfying the needs (planning), execution of the plan, and verification of its appropriateness in relation to the goal or needs. 22,[38][39][40][41][42][43] Problems in the regulation of intentional behavior also affect social...…”
mentioning
confidence: 99%
“…It is not surprising, therefore, that these patients often show enhanced emotional and motivational disturbances over time. 4 While some of these problems may reflect disturbed neurophysiology,5 others seem to be related to problems in coping with residual deficits. Clearly, both cognitive and personality disturbances, whatever the aetiology, are related to one another in traumatic head injury patients6 and are predictive of failure to return to work.…”
mentioning
confidence: 99%